MANAGEMENT OF INVESTMENT PROJECTS IN INDUSTRIAL ENTERPRISES: CHALLENGES, METHODOLOGIES, AND STRATEGIC PERSPECTIVES - PhD Associate Professor Abdurazokova Nargiza Rixsibayevna (Scholar Express Journals, 2025)
Investment project management has become one of the key determinants of competitiveness and sustainability in industrial enterprises. The increasing complexity of technological innovation, global supply chains, and financial uncertainty necessitates a systematic approach to investment planning and control. This study analyzes the management mechanisms of investment projects in industrial enterprises, identifies critical success factors, and proposes a conceptual model integrating strategic planning, financial assessment, and risk management tools. Based on empirical data and literature synthesis, the paper provides practical recommendations for improving project efficiency and sustainable development.
Keywords: Investment projects; industrial enterprises; project management